(untitled) (Research, Society and Development, 2022)
This is an integrative review of the qualitative approach literature. The following steps were followed: identification of the theme and selection of the research, elaboration of exclusion and inclusion criteria, selection of studies categorization of the selected studies, analysis and interpretation of the results. The research asked the following question: "What impacts did the COVID-19 pandemic have on the mental health of professionals working in the front line?". The studies highlight the consequences of the covid-19 pandemic on the lives of health professionals, pointing out that exposure to an emergency in public health caused occupational risk and psychological suffering due to trauma, professional devaluation, self-isolation and quarantine. This triggered several negative impacts on the mental health of professionals manifesting themselves through symptoms of insomnia, anxiety, anxiety, depression, fear, frustration and post-traumatic stress. It is concluded that, the impacts that the pandemic brought with the arrival of a new virus little known, reached directly in society and reflected in the health professionals who work in the front line, however, support and psychological care can contribute to face the effects of the pandemic on mental health, as well as other alternatives such as training courses to guide the health team in the treatment and coping with psychological problems.